2017
DOI: 10.3892/etm.2017.4369
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of antegrade intramedullary fixation for juvenile fifth metacarpal neck fracture with titanium elastic nail

Abstract: Abstract. The purpose of the current study was to assess the outcome of antegrade intramedullary fixation with titanium elastic nail (TEN) in displaced fifth metacarpal neck fractures. The present study included 69 consecutive juvenile patients with displaced fifth metacarpal fractures. The head-shaft angle of the fifth metacarpal and range of motion (ROM) of the metacarpophalangeal (MCP) joint were evaluated. A disabilities of the arm, shoulder and hand (DASH) questionnaire was used to assess upper arm functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…In comparison to the contralateral hand, almost no apex dorsal angular malformation was found. All outcomes were in close agreement with some previous studies, in which elastic intramedullary nailing was used to treat adolescents with FMNF [ 9 , 25 ]. This technique is well-suited to the small diameter of the medullary canal in adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…In comparison to the contralateral hand, almost no apex dorsal angular malformation was found. All outcomes were in close agreement with some previous studies, in which elastic intramedullary nailing was used to treat adolescents with FMNF [ 9 , 25 ]. This technique is well-suited to the small diameter of the medullary canal in adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…Contrary to the contralateral, almost no apex dorsal angular malformation was found. All outcomes were in close agreement with some previous studies, in which elastic intramedullary nailing was used to treat adolescents with FMNF [9,29]. The results proved that AIMN with K-wire is a straightforward, reliable, and minimally invasive surgical technique.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, through a summary of the postoperative imaging and joint range of motion of 55 cases, they found that ESIN treatment of metacarpal fractures could provide early restoration of joint range of motion and had a low incidence of complications. Shen et al 19 summarized 69 cases of elastic intramedullary nails for the treatment of juvenile fifth metacarpal neck fractures and proposed that anterograde insertion of elastic intramedullary nails has strong stability, induces minimal trauma, and results in almost no damage to the juvenile epiphysis. In a study by Lieber et al, 20 one patient developed nerve and tendon injury due to excessive pursuit of ESIN stability, and the authors cautioned that attention should be paid to the distance between the ESIN head and the articular surface when the ESIN needle is inserted.…”
Section: Literature Reviewmentioning
confidence: 99%